ANALYSING FACTORS THAT DRIVE CUSTOMER SATISFACTION OF GO-RIDE MANADO. - Oroh, Felly .; Lapian, S. L. H. V. Joyce; Tumbuan, Willem J.F.Alfa (Universitas Sam Ratulangi, 2017)
Abstract: Transport plays very vital role in the development of a country’s economy, indetermining overall productivity, quality of life of citizens, access to goods and services and the pattern for distributuion of economic activity. Motorcycle is one of land transport and included in the classification of types of private vehicles but nowadays motorcycles also perform the function of public transport. This kind of transportation is known as Ojek. Currently there are two kinds of ojek services, namely